2001
DOI: 10.1007/s002670010245
|View full text |Cite
|
Sign up to set email alerts
|

Toward Quantifying Water Pollution Abatement in Response to Installing Buffers on Crop Land

Abstract: The scientific research literature is reviewed (i) for evidence of how much reduction in nonpoint source pollution can be achieved by installing buffers on crop land, (ii) to summarize important factors that can affect this response, and (iii) to identify remaining major information gaps that limit our ability to make probable estimates. This review is intended to clarify the current scientific foundation of the USDA and similar buffer programs designed in part for water pollution abatement and to highlight im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
226
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(236 citation statements)
references
References 127 publications
5
226
1
4
Order By: Relevance
“…This generally depends on both the capacity of the buffer zone to promote deposition at a given site and the magnitude of the runoff load (Dosskey 2001;Helmers et al 2002). The excellent regression result (R 2 = 0.94) occurred because SF accounts for (Dosskey et al 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This generally depends on both the capacity of the buffer zone to promote deposition at a given site and the magnitude of the runoff load (Dosskey 2001;Helmers et al 2002). The excellent regression result (R 2 = 0.94) occurred because SF accounts for (Dosskey et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Many field-scale studies have shown buffers can improve water quality, and this literature is well reviewed (e.g., Fennessy and Cronk 1997;Dosskey 2001). Yet at watershed scales, where public concern about water quality is focused, the water quality impacts of conservation practices (such as buffers) are difficult to establish.…”
Section: Introductionmentioning
confidence: 99%
“…Buffer strips are vegetated zones adjacent to agroforestry or crop fields that intercept and "treat" the water draining the cropland (Dillahaet al, 1988;Dosskey, 2001). Buffer strips reduce the movement of sediment, nutrients, and pesticides from agricultural lands into the ecosystem (Borinet al, 2010;Borinet al, 2002;Patty et al, 1997;Popov et al, 2005;Rankins et al, 2001;Schmitt et al, 1999;Tingle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Contaminants from these sources are both organic or inorganic. Okache et al, (2015), Zhang et al, (2009) and Dosskey, (2001) discussed the adverse effects of these type of contaminants and how uncontrolled contamination results in decline of drinking water quality, human and animal health issues, sedimentation and degradation of aquatic ecosystem. Dauer et al, (2000) emphasizes that land use surrounding the water body influences the type of contaminants contaminating the water body; contaminants coming from industrial outlets and houses are continuous while contaminants from agricultural land use are periodic (Vega et al, 1998); so, understanding the behavior of spread of contaminates in water body will provide insight on what type of contaminants are contaminating the water and their source.…”
Section: Introductionmentioning
confidence: 99%